Does dexamethasone affect hepatic CYP450 system of fish? Semi-static in-vivo experiment on juvenile rainbow trout. (November 2015) - Burkina, Viktoriia; Sakalli, Sidika; Rasmussen, Martin Krøyer; Zamaratskaia, Galia; Koba, Olga; Thai, Giang Pham; Grabic, Roman; Randak, Tomas; Zlabek, Vladimir
Highlights: Juvenile rainbow trout were sub-chronically exposed to DEX. DEX increased CYP3A-like protein levels in fish hepatic microsomes. DEX has no effect at the highest tested concentration. DEX has no effect on studied CYP450 mediated reaction. DEX might have a negative impact on non-target species such as fish. Abstract: Effects of aquatic pollutants on fish are of increasing concern. Pharmaceutical-based contaminants are prioritized for further study in environmental risk assessment using several approaches. Dexamethasone (DEX) was one such contaminant recognised for its effect on fish health status. Thus, we carried out an in vivo experiment to identify potential effects of DEX on rainbow trout. Fish were exposed to 3, 30, 300 and 3000 ng L −1 DEX in a semi-static system over a period of 42 d. The concentrations of DEX that fish were exposed to was confirmed by LC–LC–MS/MS. Using hepatic microsomes, we determined cytochrome P450 content, activities of ethoxyresorufin O-deethylase (EROD), p-nitrophenol hydroxylase (PNPH), 7-benzyloxy-4-trifluoromethylcoumarin O-debenzylase (BFCOD) and benzyloxyquinoline O-debenzylase (BQOD), as well as protein expression. Our results showed that fish do not change the catalytic activity of CYP450-mediated reactions after high DEX concentration exposure. These results disagree with mammalian studies, where DEX is a well-known inducer of CYP450. We showed a significant effect of DEX exposure on CYP450-mediated reactions (EROD, BCFOD, BQOD and PNPH) when expressed as amount of product formed per min per nmol total CYP450 at 3, 30 and 300 ng L −1 after 21 d exposure. Moreover, BFCOD and BQ activities showed matching trends in all groups. Western blot analysis showed induction of CYP3A-like protein in the presence of the lowest environmentally relevant concentration of DEX. Based on these findings, continued investigation of the effect of DEX on fish using a battery of complementary biomarkers of exposure and effect is highly relevant.